2022
DOI: 10.3389/fonc.2022.994366
|View full text |Cite
|
Sign up to set email alerts
|

Day +60 WT1 assessment on CD34 selected bone marrow better predicts relapse and mortality after allogeneic stem cell transplantation in acute myeloid leukemia patients

Abstract: The aim of this study was to evaluate the role of WT1 expression after allogeneic stem cell transplantation (alloHSCT) in patients with acute myeloid leukemia (AML). We studied WT1 expression in bone marrow cells from 50 patients in complete remission on day +60 after transplant. WT1 was assessed on unfractionated bone marrow mononuclear cells (MNC) and on CD34+ selected cells (CD34+). A ROC curve analysis identified 800 WT1 copies on CD34+ selected cells, as the best cut-off predicting relapse (AUC 0.842, p=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Overall, our data are in line with other published papers, highlighting the role of both lineage specific molecular chimerism and WT1 as markers of MRD after allo-SCT ( 14 19 , 24 28 ). The issue of the superiority of molecular chimerism on CD34+ cells over other methods for leukemia relapse prediction is still unsolved.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our data are in line with other published papers, highlighting the role of both lineage specific molecular chimerism and WT1 as markers of MRD after allo-SCT ( 14 19 , 24 28 ). The issue of the superiority of molecular chimerism on CD34+ cells over other methods for leukemia relapse prediction is still unsolved.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it may be considered as a surrogate marker of MRD, which can be associated with a high probability of disease recurrence ( 14 17 ). Several studies have confirmed that lineage-specific molecular chimerism is a reliable marker of MRD and relapse risk ( 14 17 ), but the interplay between CD34+ chimerism and other markers of MRD (e.g., leukemic blasts detection with MFC or WT1 ) possibly associated with MRD persistence is poorly understood and under-studied ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%